Penerapan Adaptasi Perubahan Iklim melalui Sanitasi dan Konservasi Air dalam Pembangunan Berkelanjutan di RW 08 Kelurahan Gunung Anyar Tambak Kecamatan Gunung Anyar Kota Surabaya - Wirianto, Aditya Dwi; Cundaningsih, Nurvita (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Climate change has a significant impact on people's lives, particularly in terms of access to clean water and environmental sanitation. This study aims to evaluate the implementation of the Climate Village Program (ProKlim) as a form of climate change adaptation through improved sanitation and clean water provision in RW 08, Gunung Anyar Tambak Subdistrict, Surabaya City. The research employed a qualitative descriptive method through observation, interviews, and documentation. The results indicate that activities such as the construction of biopores, infiltration wells, paving, provision of household wastewater treatment systems (IPAL), healthy latrines, and access to water from PDAM and water pumps have led to an increase in the quantity of infrastructure, which is seen as a sign of improvement. Active community participation, the presence of Larvae Monitoring Cadres (Jumantik), and the use of the “Sayang Warga” application have further strengthened the early warning system for climate-related diseases. This program supports the achievement of Sustainable Development Goal (SDG) 6 and can serve as a community-based sustainable development model applicable in other areas.